2021
DOI: 10.1111/bph.15737
|View full text |Cite
|
Sign up to set email alerts
|

N‐Acylethanolamine acid amidase (NAAA) is dysregulated in colorectal cancer patients and its inhibition reduces experimental cancer growth

Abstract: Background and Purpose: N-Acylethanolamine acid amidase (NAAA) is a lysosomal enzyme accountable for the breakdown of N-acylethanolamines (NAEs) and its pharmacological inhibition has beneficial effects in inflammatory conditions. The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…By removing the junctions which output by Portcullis and TopHat, we detected some consensus cancer specific novel canonical junctions that are only found by our method. We also noticed that many genes where we detected the novel junctions are related to the prostate cancer, e.g., RANBP3L (34), NAAA (35), PYROXD2 (36), etc. Taking one of our detections, the junction from SYT17, as an example.…”
Section: Resultsmentioning
confidence: 71%
“…By removing the junctions which output by Portcullis and TopHat, we detected some consensus cancer specific novel canonical junctions that are only found by our method. We also noticed that many genes where we detected the novel junctions are related to the prostate cancer, e.g., RANBP3L (34), NAAA (35), PYROXD2 (36), etc. Taking one of our detections, the junction from SYT17, as an example.…”
Section: Resultsmentioning
confidence: 71%
“…The research of new therapeutic targets and methods for CRC has been the hot topic of cancer research. Among them, small molecule compounds that targeting novel CRC markers are one area where several progresses have been made [40][41][42][43][44]. In our study, RGS16, as a novel apoptosis suppressor in CRC, mainly inhibits the activation of TAK1-JNK/p38-mediated apoptosis signals through structural blocking.…”
Section: Discussionmentioning
confidence: 77%
“…IHC analysis from the HPA was consistent with the NAAA mRNA expression discrepancy and complemented our results. Previous studies only revealed there is a relationship between NAAA expression and tumor cell progression in bladder, prostate, and colon cancer cells (28,44,45). Unfortunately, NAAA has not been largely studied in the cancer field.…”
Section: Discussionmentioning
confidence: 99%
“…Borrelli et al. ( 28 ) displayed NAAA inhibitors can induce colorectal cancer (CRC) cell cycle arrest in the S phase and reduce cell proliferation and migration. However, the potential role of NAAA in tumorigenesis and tumor progression remains fragmentary, and there are no bioinformatics analysis systematically exploring the relationship of NAAA expression between different types of human cancers.…”
Section: Introductionmentioning
confidence: 99%